2005
DOI: 10.1108/13639510510597906
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, job stress and attitudes towards the use of force by Norwegian police officers

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
(25 reference statements)
1
32
0
1
Order By: Relevance
“…More broadly, Fabricatore et al (1978) have shown that certain personality factors, as measured by the Sixteen Personality Factor (16PF) Questionnaire, revealed that "aggressive" and "tough-minded" characteristics were consistent predictors of use-of-force. Burke and Mikkelsen (2005) as well as Phillips and Sobol (2011) subsequently found that cynical officers held more favorable attitudes towards the use-of-force, while officers reporting higher levels of professional efficacy held more favorable attitudes towards the use of social skills to solve problems. We read this body of instructive literature as suggesting that some psychological variables are important in any study of police use-of-force.…”
Section: Explaining Police Use-of-forcementioning
confidence: 94%
“…More broadly, Fabricatore et al (1978) have shown that certain personality factors, as measured by the Sixteen Personality Factor (16PF) Questionnaire, revealed that "aggressive" and "tough-minded" characteristics were consistent predictors of use-of-force. Burke and Mikkelsen (2005) as well as Phillips and Sobol (2011) subsequently found that cynical officers held more favorable attitudes towards the use-of-force, while officers reporting higher levels of professional efficacy held more favorable attitudes towards the use of social skills to solve problems. We read this body of instructive literature as suggesting that some psychological variables are important in any study of police use-of-force.…”
Section: Explaining Police Use-of-forcementioning
confidence: 94%
“…Common stressors among police are shiftwork, working overtime, overabundance of paperwork, effects on human relationships involving coworkers and family, danger associated with enforcing the law, and exposure to people in distress and pain. 5052 Emotional and physical stressors are associated with elevated cortisol levels. Police officers with high levels of post-traumatic stress disorder had higher mean awakening cortisol levels, 53 and cortisol deregulation was found in male officers with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the participants in this study are fairly representative of the members of the Police Union. Further, we refer to the study on Norwegian police of Mikkelsen et al, of which some are published [35][36][37] , who had identical questions regarding suicidal behaviour, subjective health complaint, and anxiety and depression. However, our study is not representative of the total police population, which makes it difficult to generalize from the study findings to the whole Norwegian police service.…”
Section: Strengths and Limitationsmentioning
confidence: 99%